Recording adverse events following orthopaedic trauma: Financial implications and validation of an adverse event assessment form in an Irish regional trauma unit. Issue 2 (February 2023) - Timon, Charlie; Lee, Matthew; Feeley, Iain; Quinlan, John
Highlights: Data collection in hospitals using activity-based funding models determines allocation of scarce resources. This data is collected by non-medical staff which may lead to inaccuracies. Even in smaller trauma units significant discrepancies in missed funding occur. Abstract: Background: In Ireland, funding of orthopaedic trauma is based on an activity-based funding (ABF) model. Clinically similar cases are split into diagnostic-related groups (DRG), with base funding per DRG provided. Increased complexity of cases (length of stay; complications incurred; occurrence of adverse events) attracts additional remuneration to the base funding. In our institution these adverse events are recorded via retrospective chart-abstraction methods by administrative staff. Incidences which are not included from this review affect both follow up with family physicians and patient care; as well as skewing budgetary decisions that impact fiscal viability of the service. The aim of this study was to compare a prospectively implemented adverse events form with the current national retrospective chart abstraction method. Our outcomes in terms of pay-by-results financial implications. Methods: An adverse events database adapted from a similar validated model was used to prospectively record complications in 216 patients admitted via the orthopaedic trauma service. Data was contemporaneously collected via a GDPR compliant secure medical messaging platform. Results were compared with the same cohort using an existing data abstraction method. Both data sets were coded in accordance with current standards for case funding. Results: Overall, 49 adverse events were recorded during the study through prospective charting of adverse events, compared with 26 events documented by customary method ( p <0.01).Anaemia requiring blood transfusion n  = 11 22.4%) was the most common complication, followed by delirium n  = 6 (12%), acute kidney injury n  = 6 (12%), and pneumonia n  = 5 (10.2%). Missed appropriate funding through conventional methods totalled €40, 293 . Conclusion: This pilot study demonstrates the ability to improve capture of adverse events through use of a well-designed assessment form. Proper perioperative data handling is a critical aspect of financial subsidies, enabling optimal allocation of funds.